2023
DOI: 10.1002/hsr2.1133
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health equity consideration in Cochrane systematic reviews and primary studies on urolithiasis

Abstract: Background and Aims: Health injustice is defined as "unnecessary, preventable, unjustified and unfair health differences." One of the most important scientific sources on the prevention and management of urolithiasis are Cochrane reviews in this field. Given that the first step in eliminating health injustice is to identify the causes, the aim of the present study was to evaluate equity considerations in Cochrane reviews and the included primary studies on urinary stones.Methods: Cochrane reviews on kidney sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…The proportion of primary studies set in LMICs in the present study was similar to that reported in Evans et al (38% and 37%, respectively) [22]. (As noted above, Tugwell et al reported no primary studies were set in LMICs [20]; Basirat et al reported "very few" studies were set in LMICs [21]). The proportion of studies conducted in LMICs in the present study can be considered low given that the age-standardized burden of moderate to severe hearing loss globally is higher in LMICs than high-income countries [32].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The proportion of primary studies set in LMICs in the present study was similar to that reported in Evans et al (38% and 37%, respectively) [22]. (As noted above, Tugwell et al reported no primary studies were set in LMICs [20]; Basirat et al reported "very few" studies were set in LMICs [21]). The proportion of studies conducted in LMICs in the present study can be considered low given that the age-standardized burden of moderate to severe hearing loss globally is higher in LMICs than high-income countries [32].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are similar to those of studies which investigate the reporting of health inequity in Cochrane reviews of clinical trials [20][21][22].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations